Lifestyle Variables Do Not Predict Subjective Memory Performance Over and Above Depression and Anxiety - Mascherek, Anna; Werkle, Nathalie; Göritz, Anja S.; Kühn, Simone; Moritz, Steffen (Frontiers in Psychology, 2020)
The diagnostic value of subjective cognitive complaints for cognitive functioning in a clinical setting remains unresolved today. However, consensus exists on the relation between subjective cognitive complaints (SCC) and mood variables such as anxiety and depression. Hence, SCC have also been discussed as potential proxies of psychopathology rather than representing cognitive functioning. In order to shed more light on yet still unexplained variance in subjective cognitive complaints, the relation between lifestyle variables (such as nutrition habits, exercise, alcohol consumption, smoking, quality of sleep, and Body Mass Index) and subjective complaints of selective attention as well as subjective memory performance were assessed, additionally to the influence of objective memory performance, measures of anxiety, and depression. A sample of 877 (554 women) healthy, middle-aged individuals (51 years on average, age range 35-65) was assessed in the present study. In a logistic regression framework results revealed that the effect of lifestyle variables on subjective complaints of selective attention as well as subjective memory performance was rendered non-significant. Instead, subjective complaints of selective attention and subjective memory performance were significantly determined by measures of both, anxiety and depression. One unit increase in anxiety or depression led to an increase of 6% or 15% in subjective memory performance complaints, respectively. For subjective complaints of selective attention, a one unit increase in anxiety or depression led to an increase of 11% or 26%, respectively. The strong relation between SCC and measures of depression and anxiety corroborates the notion of SCC being indicative of mental health and general well-being.